Associação entre hormônios sexuais e asma - Baldacara, Raquel Prudente de Carvalho [UNIFESP] (2016)
A relationship between oral contraceptive (OC) use and asthma is controversial and has been observed in previous researches. The objective of this study was to assess the relationship between combined OC use and pulmonary function in Brazilian women with or without asthma, in addition to evaluate the cytokines to verify the inflammatory process of asthma. This was case-control study involving women with and without asthma who were or not using combined OC. Seventy women were recruited from the Family Health Clinic or from the universities and 7 were excluded. Sixty-three patients were divided into four groups (I:-no asthma and no OC use; II:- no asthma and OC use; - III:- asthma and no OC use; and, IV: asthma and OC use). MANOVA (multivariate analysis of variance) were conducted. First one to evaluate the relationship between combined oral contraceptive (OC) use and changes in pulmonary function (FVC, FEV1, FEV1/FVC%) in women with or without asthma. The second MANOVA evaluated the influence of sex hormones on the immune system through the alteration of cytokins expression (IL-4, IL-5, and TNF-?). There was a lack of evidence regarding OC use?s effect on the spirometric parameters (Wilk?s ? = 0.850, F=0.757, p=0.647, ?²=0.053) and on cytokins levels (Wilk?s ? = 0.909, F=0.533, p=0.848, ?²=0.031), even when controlled by covariates. Therefore, this study returned lack of evidences concerning the relation between the use of OC use and alteration in spirometric parameters as well in cytokins dosages.